Treatment of unexplained facial numbness with stellate ganglion blockade: A case report - Uno Imaizumi; Satoshi Beppu; Takuro Sanuki (Clinical Case Reports, 2023)
Abstract To date, there is no established treatment for facial numbness or dysesthesia of unspecified causes. Herein, we report a case of unexplained facial numbness and confirmed hypesthesia that achieved clinical response to stellate ganglion blockade (SGB). SGB might be an effective treatment of psychological stress‐related facial numbness of unknown origin.